Production of bioethanol from cassava: Enzyme concentration study - M., Abdullah; Noorulnajwa Diyana, Yaacob; Ku Syahidah, Ku Ismail; Khairul Farihan, Kasim; M. D., Mohamed Daud (Universiti Malaysia Sabah (UMS), 2011)
Organized by Universiti Malaysia Sabah (UMS), 12th – 14th August 2009 at Novotel Hotel, 1Borneo Kota Kinabalu, Sabah, Malaysia.